The impact of obesity on urological disorder - Naravejsakul, Krittin (Health Science, Science and Technology Reviews, 2022)
The global obesity epidemic is chief among these trends in modern medical discourse. Data from the National Center for Health Statistics estimate that 39.8% of U.S. adults aged 20 years and over were obese in the year 2015 to 2016.[1] Urology is a surgical discipline that spans a variety of anatomical and metabolic systems, and is constantly influenced by global health trends in both subtle and apparent ways. Obesity, defined as a body mass index ≥ 30 kg/m2 in adults by the National Institutes of Health, is associated with an increased risk for a number of health conditions, including hypertension, unfavorable lipid level, and diabetes mellitus. More recently, there has been greater interest in the effects of obesity on a variety of benign and malignant urologic conditions. Obesity has been shown to have an effect on urolithiasis; benign prostatic hyperplasia and lower urinary tract symptoms; female incontinence, overactive bladder and pelvic prolapse; male hypogonadism; and male sexual function and infertility. These urologic diseases have a considerable impact on patients’ quality of life. Furthermore, dietary or lifestyle modification and other public health measures directed at reducing weight may reduce the incidence of urologic illnesses. More studies are necessary to determine the therapeutic effects of weight loss and dietary modification on the incidence and progression of benign and malignant urologic conditions.